2023
DOI: 10.1108/ijopm-09-2022-0581
|View full text |Cite
|
Sign up to set email alerts
|

On the drivers of drug shortages: empirical evidence from Germany

Abstract: PurposeDisruptions and shortages of drugs have become severe problems in recent years, which has triggered strong media and public interest in the topic. However, little is known about the factors that can be associated with the increased frequency of shortages. In this paper, the authors analyze the drivers of drug shortages using empirical data for Germany, the fourth largest pharmaceutical market.Design/methodology/approachThe authors use a dataset provided by the German Federal Institute for Drugs and Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(78 reference statements)
0
1
0
1
Order By: Relevance
“…Recent shortages in medical supply illustrate the importance of resilient pharma logistics networks [1,2]. The pharmaceutical industry puts high requirements on its supply chains; most notably temperature monitoring and traceability of medicinal products are a priority in order to warrant product functionality or avoid distribution of counterfeit drugs, respectively [3].…”
Section: Introduction 1circular Economies For the Reduction Of Packag...mentioning
confidence: 99%
“…Recent shortages in medical supply illustrate the importance of resilient pharma logistics networks [1,2]. The pharmaceutical industry puts high requirements on its supply chains; most notably temperature monitoring and traceability of medicinal products are a priority in order to warrant product functionality or avoid distribution of counterfeit drugs, respectively [3].…”
Section: Introduction 1circular Economies For the Reduction Of Packag...mentioning
confidence: 99%
“…In 2019, the Food and Drug Administration (FDA) found that quality issues were the leading cause of drug shortages, accounting for 62% of shortages (U.S. Food & Drug Administration 2019). These quality issues are often a result of manufacturing problems in pharmaceutical manufacturing facilities (Francas et al 2023, Jensen et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Dieser wettbewerbliche Kostendruck wird für zahlreiche Benachteiligungen und Gerechtigkeitsprobleme verantwortlich gemacht. Zuletzt wurde dies am Beispiel der Generika-Lieferengpässe im Winter 2022/2023 deutlich, die u. a. mit dem inzwischen ausgeprägten Wettbewerb der Krankenkassen um Arzneimittelrabattverträge begründet wurden [5]. Eine andere Sichtweise sieht den Wettbewerb im Gesundheitswesen als ein weitaus umfassenderes Konzept, durch das Potenziale gehoben werden, die Versorgung in allen Bereichen vor allem auch qualitativ zu verbessern.…”
unclassified